Mitigating T-cell mitochondrial dysfunction in CLL to augment CAR T-cell therapy: evaluation in an immunocompetent model - Wael Gamal; Nienke B. Goedhart; Helga Simon-Molas; Melanie Mediavilla-Varela; Angimar Uriepero-Palma; Fleur S. Peters; Kamira Maharaj; Julio C. Chavez; John Powers; Alyssa Obermayer; Timothy I. Shaw; José R. Conejo-Garcia; et al. (Blood Advances)
Abstract: An unmet clinical need in chronic lymphocytic leukemia (CLL) is emerging due to the rapidly expanding group of patients with double refractory (Bruton's tyrosine kinase- and B-cell lymphoma 2-inhibitor) disease. So far, autologous T-cell–based therapies, including chimeric antigen receptor (CAR) T cells, have limited success in CLL, which has been attributed to an acquired CLL-mediated T-cell dysfunction and subset skewing toward effector cells at the expense of memory formation. T-cell responses rely on dynamic metabolic processes, particularly mitochondrial fitness. Although mitochondrial disruptions have been observed in solid tumor–infiltrating lymphocytes, their impact on T-cell immunity in lymphoproliferative disorders is unknown. Recent findings indicate that mitochondrial mass in CAR T cells correlates with CLL clinical outcomes. This prompted our investigation into the mitochondrial fitness in CLL T cells. Integrated metabolic and functional analyses revealed impaired, depolarized mitochondria across all T-cell subsets in untreated patients with CLL, leading to further ex vivo and in vivo mouse studies on the underlying signaling alterations. Multiomics profiling of transcriptome and epigenome revealed significant alterations in mitochondrial signaling, diminished adenosine monophosphate-activated protein kinase and autophagy activity, and upregulated glycolysis coupled with hyperactivation of Akt. Inhibition of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway during CLL T-cell culture induced metabolic reprogramming, enhancing mitochondrial activity, expression of peroxisome proliferator-activated receptor-gamma coactivator 1-alpha, and memory differentiation. Underscoring clinical relevance, supplementation with the PI3Kδ inhibitor idelalisib during CAR T-cell manufacturing improved persistence and long-term leukemia-free remissions in an immunocompetent murine model. Our study suggests that modulating the abnormal CLL T-cell metabolism can enhance the efficacy of autologous T-cell therapies.